Iranian Education Center in Tbilisi (1907-1931) - Gelovani, Nani (Advances in Social Sciences Research Journal, 2026)
For centuries, Tbilisi had played a significant role in the Georgian-Iranian relations and was an important political, commercial, and cultural centre in Transcaucasia. Historically, the Iranians were one of the most significant and influential segments of the Muslim community of Tbilisi. As the general census of 1897 of the Russian Empire suggest, there were 81.700 Muslims living in Georgia (the total population of the country was 1.867.000). This period was marked by an increasing number of the Iranians in Tbilisi amounting to 6,000 people. A Consulate-General of Persia acted in the capital and there were some charity, cultural, and educational centres operation in Tbilisi as well. In 1907, Persian school (madrasa) Ettefaq-e Iraniyan (“Iranian’s union”) was established in Tbilisi by Iranian charity organization Ettefaq with under the assistance of Iran’s Consulate-General in Tbilisi and ambassador of Iran in Russia Mirza Hasan Khan Moshir od-Dowleh. The pupils at the Persian school studied the Persian, Arabic, Turkish, Georgian, French and Russian languages, as well as Sharia, geography, music, and other subjects. The school had many problems and was closed in 1931. This work is based mainly on archival materials most of which are introduced into scientific circulation for the first time.